Influence of Leadership Style, Academic Culture, Teacher Perceptions, School Status, and Teacher Gender on High School Learning Success - Syafitri, Fajar Nur; Suryaman, Maman (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study aims to test the direct influence of teacher leadership styles, teacher academic culture, teacher perception, on learning success and indirect influence through school status, and gender on learning Success in Samarinda City High School. Path analysis is used to test direct influences of free variables (leadership style, academy culture, and teacher's perception) through intervening variables. Direct influence has a greater contribution than the indirect influence of intervening school status and gender on learning success, as leadership styles, academic culture, and teacher perception have a direct and daily impact on the learning-teaching process as well as interaction with pupils.